2019
DOI: 10.21475/ajcs.19.13.05.p1565
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic potential of biofortified crisphead lettuce (Lactuca sativa) and its reaction to Root-knot nematodes

Abstract: Lettuce is the most-consumed leafy vegetable in Brazil due to its ease of preparation, nutritional quality, and affordability. Despite these benefits, there are few cultivars of crisphead lettuce (Lactuca sativa) that possess agronomic potential, high carotenoid content and resistance to nematodes. Therefore, we evaluated the agronomic potential of crisphead lettuce genotypes that are resistant to the root-knot nematode. The experiment was conducted at the Vegetable Experiment Station of the Federal Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Few researches have been conducted into the biofortified lettuce (Cassetari et al, 2015;Jacinto et al, 2019;Silveira et al, 2019;Sousa et al, 2019). One of the main obstacles is to feasibly get an individual with both good agronomic traits and high level of carotenoids (Maciel et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Few researches have been conducted into the biofortified lettuce (Cassetari et al, 2015;Jacinto et al, 2019;Silveira et al, 2019;Sousa et al, 2019). One of the main obstacles is to feasibly get an individual with both good agronomic traits and high level of carotenoids (Maciel et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Table 4). This disagreement between multivariate methods was also observed by authors who worked with the same species (Sousa et al, 2019;Jacinto et al, 2019). (Bertan et al, 2006;Araujo et al, 2016).…”
Section: Methodsmentioning
confidence: 55%
“…This demonstrates the great importance of the evaluation of the SPAD index, in the field, for future improvement programs of biofortified lettuces. Corroborating this fact, Sousa et al (2019) and Maciel et al (2019b), found values of 24.84% and 60.31%, respectively, for the same index, being the largest relative contribution among the characteristics evaluated.…”
Section: Group Codementioning
confidence: 71%
See 2 more Smart Citations